Factors That Drive Consumer Purchase Decisions at 212 Mart Lampriet Banda Aceh - Alfi Syahril Fuadi Jaya; Musfiana Musfiana; Pira Santiya (Proceedings of AICS - Social Sciences, 2021)
This study aims to determine the factors that drive consumer purchasing decisions and the dominant factors that encourage consumers to shop at 212 Mart Lampriet Banda Aceh. This research was conducted using qualitative research methods with a descriptive research type. The subjects in this study were 10 consumers of 212 Mart Lampriet; the objects of this research were the factors that encourage consumers to shop at 212 Mart Lampriet. Data was collected through observation, interviews and documentation. The data analysis used refers to the opinion of Miles and Huberman, with the stages of data reduction, data presentation, verification and drawing conclusions. The results showed that the factors that encourage consumers to shop at 212 Mart Lampriet Banda Aceh include internal factors and external factors. Internal factors are income, service, price, product, location and promotion, while external factors are cultural factors (Islamic nuances) and personal factors. The dominant factors that encourage consumers to shop at 212 Mart Lampriet Banda Aceh among external factors are culture (shades of Islam) and among internal factors are location factors.Keywords: 212 Mart, shopping, consumers, the driving factors.